Role of Tamsulosin and Solifenacin to Reduce Double J Stent Related Symptoms After Uncomplicated Ureteroscopic Lithotripsy - Basnet, Robin Bahadur; Regmi, Prabodh; Adhikari, Baikuntha; Basnet, Surendra (Nepalese Medical Journal, 2024)
Introduction: Endoscopic urological surgeries are safe procedures with further reduction in morbidity due to double J stents. Stents usually give rise to lower urinary tract symptoms and various drugs have been prescribed singly drug or in combination to ameliorate the symptoms. Since double J stenting of the ureter is one of the most common procedures in our department, we attempted to compare the efficacy of the anti-muscarinic drug Solifenacin over alpha-blocker Tamsulosin. Materials and methods: A prospective study was done where 50 consecutive patients who underwent double J stenting following ureteroscopic lithotripsy were randomized and given 5 mg Solifenacin or 0.4 mg Tamsulosin. Lower urinary tract symptoms were assessed at end of first and second week. The results were analyzed. Results: Fifty consecutive patients who underwent ureteroscopic lithotripsy were enrolled in the study. 25 of them were randomly prescribed Solifenacin and 25 were prescribed Tamsulosin based on computer generated randomization. The IPSS score was higher in the Solifenacin group, compared to the Tamsulosin group in both the first and second weeks, which was significantly higher in the first week. The reduction of symptoms within the first and second week in both groups was clinically significant, Solifenacin group being p <0.0001 and Tamsulosin group being 0.0004. Conclusions: Lower urinary tract symptoms are common and quite bothersome following DJ stent insertion. The symptoms can be ameliorated with the use of alpha blockers and anti-muscarinic drugs.